2016
DOI: 10.26226/morressier.573c1514d462b80296c98d6b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the Access AMH assay as an automated, high-performance replacement for the AMH Generation II manual ELISA

Abstract: Background: The manual Generation II (Gen II) ELISA method used to measure Anti-Müllerian Hormone (AMH) from Beckman Coulter has recently been superseded by a fully automated AMH immunoassay. The aim of this study was to evaluate the performance of the Access AMH assay and directly compare it to the modified Gen II ELISA method. A secondary aim was to verify that the fertile age-related AMH range previously established using the Gen II ELISA could be used to interpret results from the new automated Access assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…This has been shown to have very good correlation with AMH measured using the modified Gen II ELISA. 30 Indeed, it has been proposed that correlation is good enough for adult reference intervals to be interchangeable between assays, 30 although not all authors have reported a direct equivalence in values. 31 Anti-Müllerian Hormone reference interval studies have been previously described for the male and females covering the paediatric age range; 7,23,24 however, these have been based upon AMH assays which are now redundant.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown to have very good correlation with AMH measured using the modified Gen II ELISA. 30 Indeed, it has been proposed that correlation is good enough for adult reference intervals to be interchangeable between assays, 30 although not all authors have reported a direct equivalence in values. 31 Anti-Müllerian Hormone reference interval studies have been previously described for the male and females covering the paediatric age range; 7,23,24 however, these have been based upon AMH assays which are now redundant.…”
Section: Discussionmentioning
confidence: 99%
“…There are issues with standardization and harmonization of assays in use. [96][97][98][99][100][101][102] AMH is secreted into blood by small antral follicles. During the menstrual cycle, AMH concentrations are stable.…”
Section: Steroid Analysismentioning
confidence: 99%
“…All blood samples were processed using the Beckman Coulter manual Generation II ELISA (enzyme‐linked immunosorbent assay) method or the superseding automated Access AMH immunoassay. These assays have been demonstrated to have highly correlated results ( R 2 = 0.9822) making this data interchangeable without conversion …”
Section: Methodsmentioning
confidence: 99%